Folic acid-mediated targeting of cowpea mosaic virus particles to tumor cells - Destito, Giuseppe (2007)
Cowpea mosaic virus (CPMV) is a well-characterized nanoparticle that has been used for a variety of nanobiotechnology applications. CPMV interacts with several mammalian cell lines and tissues in vivo. To overcome natural CPMV targeting and re-direct CPMV particles to cells of interest, we attached a novel folic acid-PEG conjugate using the copper-catalyzed azide-alkyne cycloaddition reaction. PEGylation of CPMV completely eliminated background binding of the virus to tumor cells. The PEG-folate moiety allowed CPMV specific recognition of tumor cells bearing the folate receptor. In addition, by testing CPMV formulations with different amounts of the PEG-FA moiety displayed on the surface, we show that higher-density loading of targeting ligands on CPMV may not be necessary for efficient targeting to tumor cells. These studies help to define the requirements for efficiently targeting nanoparticles and protein cages to tumors.